Table of Content - - (Journal of Islamic Sciences, 2025)
Table of Content: • Jurisprudential Choices for Resolving Madhhab Disagreements in Selected Prayer Rulings The Imam Abu Ḥanīfa Mosque (may Allah have mercy on him) as a Model: An Inductive Comparative Study Asst-Prof. Ammar AbdulHussein Asham • The Tunisian School of Jurisprudence and the Theory of its Moderate Line Dr. Abdennabi Mohammad Esgheir Al-Houssaini • The stability of the Doctrinaire inference of Ahl Asunna wal Jama’ah - An Applied Fundamental Study Ms. Halimah Fayiz Alasmari, Co-Prof. Latifah Abdulaziz Almayouf • The Shi‘a Position Toward the Three Rightly Guided Caliphs (May Allah Be Pleased with Them) Through Their Method of Interpreting the Qur’an by the Qur’an: A Theological Study Ms. Huda abdullah al-Damigh ,Prof. Sahl Raffāʿ al-ʿOtaibii • The Concept of Provision in the Holy Quran (A Semantic-Exegetical Study) Asst-Prof. Asmaa Wajeh Younis • Envy and the Destruction of the Quraysh at Badr Dr. Ouedraogo Inoussa (Yunus)